2020
DOI: 10.3390/foods9010063
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Perceptions and Sensory Properties of Beef Patty Analogues

Abstract: The present study was carried out to gain consumer insights on the use of tempeh (a fermented soy bean product) to improve the healthiness of beef patties and to determine the acceptable level of tempeh (10%, 20%, or 30%) in the patty. The study consisted of conducting two focus groups (n = 15), a pilot sensory evaluation, and a full consumer sensory study. The focus groups were asked about their consumption of beef patties, attitudes towards processed meat, attitudes towards negative aspects of red meat consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Consumer studies have shown that unlike meat-free products, hybrid beef burgers and pork sausages were not significantly different from the full-meat alternatives in terms of sensory attributes [ 114 ]. A replacement of beef with 10% tempeh resulted in a juicier and more tender patty than the full-meat control, and was similar in terms of overall acceptability and flavour [ 163 ]. Another consumer study conducted in the United States, Spain, and Mexico found that cookies made with 15% cricket flour replacement fared similar to the control in terms of appearance, colour, and aftertaste, and consumers in Spain and Mexico significantly preferred the 15% cricket flour cookie [ 164 ].…”
Section: Gaps and Opportunitiesmentioning
confidence: 99%
“…Consumer studies have shown that unlike meat-free products, hybrid beef burgers and pork sausages were not significantly different from the full-meat alternatives in terms of sensory attributes [ 114 ]. A replacement of beef with 10% tempeh resulted in a juicier and more tender patty than the full-meat control, and was similar in terms of overall acceptability and flavour [ 163 ]. Another consumer study conducted in the United States, Spain, and Mexico found that cookies made with 15% cricket flour replacement fared similar to the control in terms of appearance, colour, and aftertaste, and consumers in Spain and Mexico significantly preferred the 15% cricket flour cookie [ 164 ].…”
Section: Gaps and Opportunitiesmentioning
confidence: 99%
“…However, the addition of dry ingredients may directly affect tenderness, softness, and juiciness. Previous research reported that patties formulated with breadcrumbs and soy protein isolate were found to be chewier and less tender when compared to patties formulated with beef only [41,42]. The TE powder used in this research had 82.5% dry matter, and was thus a very dry ingredient.…”
Section: Discussionmentioning
confidence: 93%
“…Consumer response to reformulated burger patties with ingredients that could improve healthfulness [4] is another topic area in this Special Issue. Taylor et al [4] tested various levels of tempeh inclusion (10%, 20%, and 30%) in beef patties.…”
mentioning
confidence: 99%
“…Consumer response to reformulated burger patties with ingredients that could improve healthfulness [4] is another topic area in this Special Issue. Taylor et al [4] tested various levels of tempeh inclusion (10%, 20%, and 30%) in beef patties. Their sensory experiments revealed that beef patties could include up to 10% tempeh; however, consumers rated visual appearance lower, along with less flavor and overall acceptability when patties included 20% to 30% tempeh [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation